2019
DOI: 10.1007/s12015-019-09917-z
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Mesenchymal Stem Cells to Neuroglia: in the Context of Cell Signalling

Abstract: The promise of engineering specific cell types from stem cells and rebuilding damaged or diseased tissues has fascinated stem cell researchers and clinicians over last few decades. Mesenchymal Stem Cells (MSCs) have the potential to differentiate into non-mesodermal cells, particularly neural-lineage, consisting of neurons and glia. These multipotent adult stem cells can be used for implementing clinical trials in neural repair. Ongoing research identifies several molecular mechanisms involved in the speciatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 159 publications
(180 reference statements)
0
45
0
Order By: Relevance
“…Adipose tissue is an abundant source of MSCs, and AT-MSCs can differentiate toward adipogenic, chondrogenic, and osteogenic cell lineages. Recent studies showed that AT-MSCs have the potential to differentiate into nonmesodermal cells such as neural cells, hepatocytes, and pancreatic beta cells [ 20 24 ]. Therefore, new strategies for the treatment of DM using AT-MSCs that differentiated into IPCs have been actively researched [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue is an abundant source of MSCs, and AT-MSCs can differentiate toward adipogenic, chondrogenic, and osteogenic cell lineages. Recent studies showed that AT-MSCs have the potential to differentiate into nonmesodermal cells such as neural cells, hepatocytes, and pancreatic beta cells [ 20 24 ]. Therefore, new strategies for the treatment of DM using AT-MSCs that differentiated into IPCs have been actively researched [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, differentiation of neurons from MSCs was reported in different ways such as using co-culture conditions, exosomes and graphene substrates [13][14][15]. Neuronal differentiation attempts of MSCs in media containing chemical reagents provided a faster differentiation rate compared to other methods [16]. The most accaptable identifiers of neuronal differentiation are morphological changes and neuronal gene expression profiles.…”
Section: Introductionmentioning
confidence: 99%
“…For in vitro differentiation of stem cells into neuronal precursors we used either commercially available ready-made neuronal medium with no fetal bovine serum, containing neuronal-specific GFs and penicillin/streptomycin, or have prepared a culture medium from Dulbecco's Modified Eagle's medium (DMEM) to which we added neuronal GFs BDNF, IGF-1, ascorbic acid and aminophylline, which is in line with established neuronal differentiation protocols ( 44 ). Fig.…”
Section: Treatmentmentioning
confidence: 99%